Divine Domesticities - Choi, Hyaeweol (ANU Press, 2014)
Divine Domesticities: Christian Paradoxes in Asia and the Pacific fills a huge lacuna in the scholarly literature on missionaries in Asia/Pacific and is transnational history at its finest.